Designing an efficient storage location assignment approach for through-flow warehouses - Görür, Fırat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Order placement and retrieval operations in a warehouse with separated incom ing and outgoing storage handling areas are analyzed. An approach, which consists of a model and a heuristic algorithm, is devised in order to determine how stock keeping units could be assigned to the storage locations so that the total distance traveled is optimized. All necessary data for the model are generated. Because of the complexity of the problem, a new model with a reformulated objective function, which is derived from number of occurrences in the same SKUs entries and retrievals, is defined to be minimized instead of the SLAP itself. In the objective function; movements between storage handling area of the incoming SKUs and storage locations during the place ment operations, movements between the storage handling area of outgoing SKUs and storage locations during the retrieval operations, and movements between the storage locations during the picking operations are included as three components. After model ing, the problem is solved by a heuristic algorithm. Computational results are obtained by 42 different scenarios. The results reveal that good improvements are obtained by the approach, especially when there is no capacity constraint for stock handlers.
Keywords: Storage rings.